Automated Deduction - CADE 28 28th International Conference on Automated Deduction, Virtual Event, July 12-15, 2021, Proceedings - Platzer, André; Sutcliffe, Geoff (Lecture Notes in Computer Science; Lecture Notes in Artificial Intelligence, 2021)
This open access book constitutes the proceeding of the 28th International Conference on Automated Deduction, CADE 28, held virtually in July 2021. The 29 full papers and 7 system descriptions presented together with 2 invited papers were carefully reviewed and selected from 76 submissions. CADE is the major forum for the presentation of research in all aspects of automated deduction, including foundations, applications, implementations, and practical experience. The papers are organized in the following topics: Logical foundations; theory and principles; implementation and application; ATP and AI; and system descriptions.